Innovative Raw Material for Crackers: Unhairing Durable Dry Salt-Cured Skin with Elephant Grass IMO - Ari Muslim Ramadhan; Deni Novia (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Dry salt-cured skin is an alternative material for standard shrimp crisp skin, but it is difficult to discard to discard hair. The alternative is to use indigenous microorganisms (IMO) of elephants grass (Pennisetum purpureum), which contain protease enzymes that help the waste process hair. This research aims to determine the effect of using grass elephant IMO in unhairing on dry salt-cured skin with various soaking times cow skin to physicochemical and sensory tests. This research uses the method experiment with a completely randomized design, which consists of five treatments and four repetitions. The treatments were soaking the cow skin in a solution of grass elephant IMO for 12-60 hours. The parameters observed are rate water, rate proteins, texture, lightness (L*), and sensory test (cleanliness of hair, cleanliness of skin, and skin color). The results of the study showed that the length of soaking the skin using IMO elephant grass in the unhairing process had no significant effect (P>0.05) on moisture content, protein content, texture, and lightness (L*) but had a significant effect (P<0.05) on the sensory test; fur cleanliness, skin cleanliness, and color. Results best on study This is on immersion during 24 O'clock with an average rate of water 64.76%, rate proteins 31.51%, texture 56.88h, lightness (L*) 45.81 and sensory test; cleanliness hair 3.97 (clean), cleanliness skin 3.94 (clean), and color 4.63 (sand).